Penerapan Design Thinking Dalam Inovasi Tempat Bertransaksi Jual Beli Barang Pada Toko Online Thrifter.Things (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2021)
The purpose of this study is to analyze the application of design thinking in designing appropriate solutions and innovations to the problems found in the thrifter.things online store, especially on the problem of buying and selling transactions (buying and selling platforms). This research method uses descriptive research methods and design thinking methods, namely research that aims to describe a situation or phenomenon that is currently happening by using scientific procedures to solve problems. The results of this study indicate that at the Emphatize stage the process and place for thrifter.things transactions are irregular, at the Determine stage only one platform is needed that is used as a special place for transactions, at the Ideate Thifter.things stage you can use the platform's website as the main place to sell buy products, at the Prototype stage because the website is an innovative idea to improve the buying and selling transaction process at the Thrifter.things online store which will be used as the only place for transactions, and in testing the use of the website as a potential land for doing business online.